Assessment of microfilaremia in 'hotspots' of four lymphatic filariasis endemic districts of Nepal during post-MDA surveillance. - Pramod Kumar Mehta; Mahendra Maharjan (Public Library of Science (PLoS), 2024)
Background The lymphatic filariasis (LF) elimination program in all sixty-three endemic districts of Nepal was based on annual mass drug administration (MDA) using a combination of diethylcarbamazine (DEC) and albendazole for at least 5 years. The MDA program was started in the Parsa district of the Terai region and at least six rounds of MDA were completed between 2003 and 2017 in all filariasis endemic districts of Central Nepal. Transmission Assessment Survey (TAS) report indicated that circulating filarial antigen (CFA) prevalence was below the critical value i.e., ≤ 2% in selected LF endemic districts of Central Nepal. Based on the TAS report, antigen-positive cases were found clustered in the foci of those districts which were considered as "hotspots". Hence the present study was designed to assess microfilaremia in hotspots of four endemic districts of Central Nepal after the MDA program. Methodology and principal findings The present study assessed microfilaremia in hotspots of four endemic districts i.e. Lalitpur and Dhading from the hilly region and Bara and Mahottari from the Terai region of Central Nepal. Night blood samples (n = 1722) were collected by finger prick method from the eligible sample population irrespective of age and sex. Community people's participation in the MDA program was ensured using a structured questionnaire and chronic clinical manifestation of LF was assessed using standard case definition. Two districts one each from the hilly region (Lalitpur district) and Terai region (Bara district) showed improved microfilaria (MF) prevalence i.e. below the critical level (<1%) while the other two districts are still over the critical level. There was a significantly high prevalence of MF in male (p = <0.05) and ≥41 years of age group (p = <0.05) community people in the hotspots of four endemic districts. People who participated in the previous rounds of the MDA program have significantly low MF prevalence. The upper confidence limit of MF prevalence in all hotspots of four districts was above the critical level (>1%). Chronic clinical manifestation of LF showed significant association with the older age group (≥41 years) but not with sex. Conclusions The study revealed LF transmission improved in hotspots of two districts while continued in others but the risk of LF resurgence cannot be ignored since the upper confidence level of MF prevalence is over 1% in all the hotspots studied districts. High MF prevalence is well correlated with the number of MDA rounds but not with the MDA coverage. Community people involved in MDA drug uptake in any previous and last rounds have significantly less MF infection. Hence it is recommended that before deciding to stop the MDA rounds it is essential to conduct the MF survey at the hotspots of the sentinel sites.